Efficacy Evaluation of 755-nm Long-Pulse Alexandrite Laser Combined with 0.5% Timolol Maleate Eye Drops in the Treatment of Thicker Infantile Hemangioma - Wu J; Zhou F; Gao Y (Dove Medical Press, 2021)
Jianming Wu,* Fangyan Zhou,* Yu Gao Department of Dermatological, Yuying Children's Hospital, The Second Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, 325000, People's Republic of China*These authors contributed equally to this workCorrespondence: Yu Gao Email 570875734@qq.comPurpose: Assessment of the clinical effectiveness and safety of 755-nm long-pulse alexandrite laser combined with 0.5% timolol maleate eye drops in treating thicker infantile hemangioma (IH).Materials and Methods: Retrospective analysis of IH treated with 755-nm long-pulse alexandrite laser and topical timolol in the Second Affiliated Hospital of Wenzhou Medical University from October 2019 to October 2020. Seventy-eight cases were included, with a five-week laser treatment interval. Treatment status was documented during the 35 weeks before each treatment, the effect was assessed at the visual analog scale (VAS), and side effects were recorded. During the 6-month follow-up period, the recurrence and residual skin lesions were monitored. The relationship between IH thickness, treatment duration and VAS was analyzed.Results: Among the 78 children with hemangioma, 4 children were treated with a combination of propranolol, fractional laser and cinnamyl alcohol injection due to poor curative effect. Finally, the lesions were effectively alleviated. At the 5th, 15th, 25th, and 35th weeks of treatment, the average VAS of 74 children were 3.56 ± 1.20, 4.61 ± 1.43, 5.63 ± 1.60, and 6.63 ± 1.72, respectively. We analyzed VAS in different thickness groups with Repeated Measures Analysis of Variance(RMANOVA). The results show that the VAS of the thickness 2- 3 mm and 3- 5mm groups were higher than the 5- 7mm and 7- 8mm groups (F group = 440.54, P < 0.05, F time = 448.31, P < 0.05). During the 6-month follow-up period, none of the 74 children relapsed and the residual skin lesions gradually vanished.Conclusion: Combined treatment of IHs with a 755-nm long-pulse alexandrite laser and 0.5% timolol maleate eye drops which has apparent clinical efficacy and safety reduce residual skin lesions and decrease the IH recurrence rate.Keywords: infantile hemangioma, 755-nm long-pulse alexandrite laser, timolol maleate eye drops, thick